The socratic method for creativity, critical thinking and sustainable development (2017)
In Nigeria today, there is a growing need for individuals to think in divergent ways to solve the nation’s social and economic challenges, and bring about desired growth. Education has been seen as the bedrock of development in any society. This paper takes a critical look at the Socratic method of imparting knowledge and how it can help learners to build creative ability that can lead to sustainable development in the society. Socrates stated that ideas are formed from the mind and with systematic questioning, man can reason out Solutions to life bordering issues in order to create, innovate as well as proffer Solutions to society's problems. This paper examines Socrates' dialogue with Menno, about a slave boy who was able to solve geometric equation without being taught by a teacher. The paper did not suggest a policy or skill, rather it emphasised the role of a teacher in helping to draw out or lead out the hidden potentials innate in man